Legal Protection for Consumers Against Food Products that are not Halal Certified Based on Law Number 33 of 2014 - Ribut Widiono; M. Shidqon Prabowo; Bahrul Fawaid (JURNAL AKTA, 2025)
This study aims to analyze the legal protection provided to consumers against the circulation of food products that are not halal certified based on Law Number 33 of 2014 concerning Halal Product Assurance. The certification process involves three main institutions: the Halal Product Assurance Organizing Agency as the organizing authority, the Halal Inspection Institute as the inspection and testing institution, and the Indonesian Ulema Council as the institution that issues fatwas on halal product certification. Legal protection for Muslim consumers is reflected in the principles of protection, responsibility, and transparency of information, which are strengthened by reporting mechanisms and the imposition of sanctions on violating business actors. This study uses a normative juridical approach with descriptive analysis of legal norms to examine the provisions, enforcement mechanisms, and implications of the Halal Product Assurance Law for consumer protection. The results show that although the Halal Product Assurance Law provides a strong legal basis, its implementation is still hampered by weak supervision, lack of socialization, and limited coordination between institutions. Therefore, it is necessary to strengthen Halal Product Assurance Organizing Agency, increase public awareness, and align halal policies with consumer protection regulations to ensure legal certainty and public trust.